Factors That Influence The Couples Of Childbearing Age On Selection Of Iud Contraception - Ratna (Journal of Applied Nursing and Health, 2020)
The low use of IUD (Intrauterine device) contraception is due to ignorance of acceptors about the advantages of the method. The selection of IUD contraception can be influenced by the level of knowledge, age, and family support in the selection of contraception that is appropriate. Objective: Knowing the Factors that Influence the couples of childbearing age on IUD Contraception Selection in the Lakea Community Health Center Working Area in Lakea Buol District. The design used in the study was correctional analytic. The population is all fertile age couples. The sample size is 32 respondents using Simple Random sampling technique. Independent variables of research ware myrrh, knowledge, and family support. The dependent variable was the selection of an IUD. Data was collected using a questionnaire, then the data were analyzed using logic regression test, with a significance level of α ≤ 0.05. The results showed that most of the respondents aged 20-35 years were 18 respondents (48.6%), sufficient knowledge as many as 15 respondents (46.9%), assessment of moderate family support as many as 15 respondents (46.9%) , using other than IUD as many as 22 respondents (22%). The results showed that p <a with a value of <0.25, this can be seen in Overall Statistics with a significance value of (p) 0.003 which means that there are variables that affect the selection of IUD KB, and se When seen (p) in each -one of the independent variables namely the age variable has a value (p) of 0.004) knowledge has a value (p) of 0.002, the knowledge variable has a value (p) of 0.001. Family support has a positive influence in the form of information, instrumental assistance, emotions, and assessment given to the selection of IUD contraception by family members.